Myiasis in Children: Fly Larval Infestation - Meena, SS; Meena, D (Journal of Nepal Paediatric Society, 2015)
Human myiasis is a parasitic infestation by fly larvae in poor hygienic or immunocompromised children’s. We present here two case of fly larval infestation including one scalp myiasis in six year old male street child and other one vulvar myiasis in 18 year old unmarried girl suffering from insulin dependent diabetes mellitus and psychiatric illness. J Nepal Paediatr Soc 2014;34(3):244-246 DOI: http://dx.doi.org/10.3126/jnps.v34i3.10289